Midnight is a place - Aiken, Joan. (London : Red Fox, 1974)
Fourteen year-old- Lucas leads a lonely, monotonous life in the house of his unpleasent guardian until the unexpected arrival of an unusual little girl presages a series of event that completely change his life.
Keywords: England -- Fiction